Dawn R. Bazely, John Reynolds, Sue and another Field researcher stand together at Camp Finney - Bazely, Dawn (1983)
Dawn R. Bazely, John Reynolds, Sue and another Field researcher stand together at Camp Finney,Wapusk National Park in front of many gas drums. Just beyond the gas drums a water body and large expanses of grassland can be seen